Implementasi Media Wordwall terhadap Minat Belajar Siswa dalam Pembelajaran Pendidikan Pancasila di SMK Negeri 2 Semarang - Fatkhan Yusuf Anggulian; Supriyono Purwosaputro; Puput Tri Hartanti (Departement of Mathematics Education, 2024)
The learning media used by teachers in the classroom today is very important for teachers to use so that learning can take place in an interesting way. One of them is Wordwall media. This research aims to determine students' interest in learning by using media word wall in learning Pancasila Education at SMK N 2 Semarang. This research study uses a qualitative descriptive approach. This research collects data using observation, documentation and questionnaires conducted in Class X AKL 3 SMK N 2 Semarang. Researchers to process the analyzed data. Media Implementation research results word wall Regarding students' learning interest in learning Pancasila education at SMK Negeri 2 Semarang, it shows that the use of Wordwall in learning Pancasila education increases students' interest in learning and student participation so that learning is more interesting and enthusiasm for learning is higher. It is hoped that this research can provide knowledge so that Pancasila education learning can use currently developing technology.